PENGEMBANGAN “FUNCTION MOBILE: FRACTION SERIES” UNTUK PENGENALAN KONSEP BILANGAN PECAHAN [DEVELOPMENT OF “FUNCTION MOBILE: FRACTION SERIES” FOR INTRODUCTION TO FRACTIONAL NUMBER CONCEPTS] - Elvaretta, Nathania Dea; Setyadi, Danang (JOHME: Journal of Holistic Mathematics Education, 2025)
Students' low understanding of the concept of fractions is often caused by the abstract nature of the material and the use of conventional learning media that are less interesting. The development of learning media nowadays needs to be adjusted to the ability of students who are capable of using smartphones as learning tools. Therefore, the purpose of this research is to create Android-based math learning media that can help third-grade elementary school students in recognising fractions. This learning media is in the form of an Android game named "Function Mobile: Fraction Series." The main focus of this game is to recognise and visualise fractions that match the questions at each level. The type of research used is Research and Development, by implementing the ADDIE model in all stages of media creation. The ADDIE development process includes product analysis (needs analysis and performance analysis), learning media design, media development, implementation of development results, and evaluation through product trials. The results of this study indicate that the game Function Mobile: Fraction Series is very feasible to use as learning media. This can be seen from the average percentage of validity of 96% very valid criteria and the average percentage of practicality obtained of 97% with very practical criteria. Thus, the game Function Mobile: Fraction Series is valid and practical to use as an alternative learning media. BAHASA INDONESIA ABSTRACT: Rendahnya pemahaman siswa terhadap konsep bilangan pecahan seringkali disebabkan oleh sifat materi yang abstrak dan penggunaan media pembelajaran konvensional yang kurang menarik. Pengembangan media pembelajaran saat ini perlu disesuaikan dengan kemampuan siswa yang telah cakap menggunakan smartphone sebagai alat pembelajaran. Media pembelajaran ini berbentuk game android yang diberi nama "Function Mobile: Fraction Series." Fokus utama permainan ini adalah mengenal dan memvisualisasikan pecahan yang sesuai dengan pertanyaan pada setiap levelnya. Oleh karena itu, tujuan dari penelitian ini adalah menciptakan media pembelajaran matematika berbasis android yang dapat membantu siswa kelas III SD dalam mengenal bilangan pecahan. Jenis penelitian yang digunakan adalah Research and Development, dengan mengimplementasikan model ADDIE dalam seluruh tahap pembuatan media. Proses pengembangan ADDIE mencakup analisis produk (analisis kebutuhan dan analisis kinerja), perancangan media pembelajaran, pengembangan media, implementasi hasil pengembangan, dan evaluasi melalui uji coba produk. Hasil dari penelitian ini menunjukkan bahwa game Function Mobile: Fraction Series sangat layak untuk digunakan sebagai media pembelajaran. Hal ini dapat dilihat dari rata-rata persentase kevalidan sebesar 96% kriteria sangat valid dan rata-rata persentase kepraktisan yang diperoleh sebesar 97% dengan kriteria sangat praktis. Dengan demikian game Function Mobile: Fraction Series valid dan praktis digunakan sebagai alternatif media pembelajaran.